In vitro concentration optimization of ethanol extract from Makasar fruit seeds (Brucea javanica L. Merr) as an anti-inflammatory agent - Diva Almira; Windah Anugrah Subaidah; Agus Dwi Ananto; Rizqa Fersiyana Deccati; Handa Muliasari (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
Anti-inflammatory medications are necessary to treat excessive inflammation reactions due to injury, infection, or irritation. The emergence of several adverse effects associated with synthetic anti-inflammatory drugs has prompted the continued use of anti-inflammatory agents derived from natural products with low side effects and a high therapeutic effect. While it is well established that the seeds of the Makassar fruit (Brucea javanica (L.) Merr.) ÃÂ have anti-inflammatory activity, the optimal concentration of Makasar fruit seed extract for anti-inflammatory activity is unknown. This study aims to determine the optimal Makassar fruit seed extract concentration as an in vitro anti-inflammatory. The seeds of the Makasar fruit were extracted using the sonication method (3 x 35 minutes) in 96% ethanol and then concentrated using a rotary evaporator. The secondary metabolites of Makasar fruit seed extract were then identified in the test tubes, and the anti-inflammatory activity was determined using the protein denaturation inhibition method. The results indicated that the extract produced had a yield of 10.03%. The Makassar fruit seed extract contains secondary metabolites of phenolics, flavonoids, and terpenoids. Makasar fruit seed extract exhibited the optimum anti-inflammatory activity at a concentration of 1%, with a 55.47%ÃÂ inhibition of protein denaturation.